2015
DOI: 10.1534/genetics.112.145540
|View full text |Cite
|
Sign up to set email alerts
|

Actin and Endocytosis in Budding Yeast

Abstract: Endocytosis, the process whereby the plasma membrane invaginates to form vesicles, is essential for bringing many substances into the cell and for membrane turnover. The mechanism driving clathrin-mediated endocytosis (CME) involves > 50 different protein components assembling at a single location on the plasma membrane in a temporally ordered and hierarchal pathway. These proteins perform precisely choreographed steps that promote receptor recognition and clustering, membrane remodeling, and force-generating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
233
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(249 citation statements)
references
References 428 publications
(650 reference statements)
4
233
0
6
Order By: Relevance
“…Kymograph analysis revealed that cell elongation in LatA-treated sty1Δ and wis1Δ cells gradually declines over time (Figure 2B). This could be explained as follows: (1) in the initial period after LatA treatment, tip-localized active Cdc42 can drive cell elongation through positive regulation of exocytosis [29]; (2) however, after LatA treatment, membrane proteins involved in exocytosis would no longer be recycled by endocytic retrieval from the plasma membrane, because endocytosis in yeasts depends on the actin cytoskeleton [30]; and therefore (3) such proteins will eventually be depleted from cytoplasmic pools, ultimately leading to cessation of elongation.…”
Section: Resultsmentioning
confidence: 99%
“…Kymograph analysis revealed that cell elongation in LatA-treated sty1Δ and wis1Δ cells gradually declines over time (Figure 2B). This could be explained as follows: (1) in the initial period after LatA treatment, tip-localized active Cdc42 can drive cell elongation through positive regulation of exocytosis [29]; (2) however, after LatA treatment, membrane proteins involved in exocytosis would no longer be recycled by endocytic retrieval from the plasma membrane, because endocytosis in yeasts depends on the actin cytoskeleton [30]; and therefore (3) such proteins will eventually be depleted from cytoplasmic pools, ultimately leading to cessation of elongation.…”
Section: Resultsmentioning
confidence: 99%
“…albicans strains lacking ARP2 or ARP3 have dramatic actin cytoskeleton defects and delayed rates of endocytosis [17]. A common feature of cells with endocytic defects and depolarized actin patches is hyperactivity of cell wall stress pathways [19]. We assessed whether the mutants in our study also exhibited endocytic defects accompanying the activation of cell wall stress.…”
Section: Resultsmentioning
confidence: 99%
“…Such clarification should have significance far beyond the understanding of Chlamydomonas itself, as this alga can now serve as an experimentally tractable representative not only of the plant superkingdom (where genetic studies of actin function are challenging because of the multitude of actin genes) but also of at least some fraction (Rogozin et al 2009) of the vast majority of the eukaryotic world that lies outside of the opisthokonts (animals, fungi, and their close relatives), where most studies of actin function have been done. For example, is the role of actin in endocytosis, well documented in the opisthokonts (Goode et al 2015), universal (and thus presumably ancestral) in eukaryotes more generally? Does the formation of cleavage furrows (which is nearly universal in eukaryotes other than higher plants) always involve actin (Balasubramanian et al 2012), even though type-II myosin (a component of the opisthokont actomyosin ring) is not present in groups other than the opisthokonts and their "close" relatives the amoebozoa (Richards and Cavalier-Smith 2005)?…”
Section: Discussionmentioning
confidence: 99%